The moderating role of HR practices on the career adaptability-job crafting relationship: a study among employee-manager dyads - Federici, Eloisa; Boon, Corine; Den Hartog, Deanne N. (International journal of human resource management, 2021)
This study aims to investigate whether career adaptability could enhance an employee's work engagement through job crafting behaviors and to address the role of HR practices in this relationship. Based on career construction theory, we first examine whether career adaptability, as a self-regulatory competency may trigger enhanced job crafting behaviors, which in turn increase employee's work engagement. Second, we propose a moderation model in which different implemented high-performance work practices (HPWPs) moderate the relationship between career adaptability and job crafting. The results show that job crafting mediated the positive relationship between career adaptability and work engagement. The results support the hypothesized moderation only for opportunity-enhancing HPWPs. The relationship between career adaptability and job crafting is positive and significant for medium and high opportunity-enhancing HPWPs, but not for low levels of this HPWPs domain. The results imply that through the implementation of opportunity-enhancing HPWPs organizations can create a room for employees to express their adaptability at work through crafting their jobs, which in turn relates to work engagement.